2006
DOI: 10.1371/journal.pmed.0030272
|View full text |Cite|
|
Sign up to set email alerts
|

Frequency of Adverse Events after Vaccination with Different Vaccinia Strains

Abstract: BackgroundLarge quantities of smallpox vaccine have been stockpiled to protect entire nations against a possible reintroduction of smallpox. Planning for an appropriate use of these stockpiled vaccines in response to a smallpox outbreak requires a rational assessment of the risks of vaccination-related adverse events, compared to the risk of contracting an infection. Although considerable effort has been made to understand the dynamics of smallpox transmission in modern societies, little attention has been pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 34 publications
0
62
0
3
Order By: Relevance
“…43 Furthermore, the vaccine Copenhagen strain was approved for human vaccine use in Denmark and the Netherlands. 44 A recombinant of the Copenhagen strain expressing the rabies virus glycoprotein was constructed by the insertion of the encoding cDNA in the TK locus. 45 This recombinant has received a conditional commercial license in both Europe and in the United States.…”
Section: Oncolytic Vaccinia Virus Expressing Fcu1 J Foloppe Et Almentioning
confidence: 99%
“…43 Furthermore, the vaccine Copenhagen strain was approved for human vaccine use in Denmark and the Netherlands. 44 A recombinant of the Copenhagen strain expressing the rabies virus glycoprotein was constructed by the insertion of the encoding cDNA in the TK locus. 45 This recombinant has received a conditional commercial license in both Europe and in the United States.…”
Section: Oncolytic Vaccinia Virus Expressing Fcu1 J Foloppe Et Almentioning
confidence: 99%
“…This was achieved without a real understanding of the immunology underlying the protection. The risk of adverse reactions associated with live vaccinia [1,2] led to the eventual withdrawal of the licensed Dryvax ® vaccine from general use in 1972, although the potential re-emergence of smallpox as a weapon of bioterrorism has sparked renewed interest in vaccinia and the development of safer alternatives, such as the attenuated modified virus Ankara (MVA) strain. The immunological basis of protection against smallpox afforded by vaccinia is now being re-examined using modern genetic, immunological and proteomic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these health risks, vaccination is contraindicated in pregnant women, the immunocompromised, and in persons with dermatological abnormalities, such as eczema [7][8][9]. Kretzschmar et al recently reported that the frequency of death associated with vaccination might be higher than previously believed [10]. To diminish these health risks, attenuated VACV viruses, such as modified vaccinia Ankara (MVA) and LC8m16 have been developed [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%